Pola Penerapan Strategi Hilirisasi Produk Turunan Jamur Tiram untuk Pangan Substitusi Nasi - Susanto, Hendra; Witjoro, Agung; Fitriyati, Umi; Izza, Jasmine Nurul; Aruna, Alby; Oktavia, Silvi Tri (IAI Nasional Laa Roiba Bogor, 2024)
The application pattern of downstream strategies for oyster mushroom derivative products as rice substitute food is an innovative initiative aimed at enhancing the value of oyster mushrooms as an alternative food source. This study examines the process of processing oyster mushrooms into various rice substitute products, such as mushroom flour, mushroom rice, and other processed products. The methods used include technical training, product trials, and market analysis. The results show that oyster mushroom derivative products have high potential as a healthy and nutritious food alternative. The potential and problems in the field were identified through the Participatory Rural Appraisal (PRA) method. Meanwhile, the implementation pattern consists of market identification and analysis, product development, production and operations, distribution and logistics, marketing strategy, and continuous evaluation & development. Collaboration between government, academics and the private sector is very important in supporting the development of the oyster mushroom industry and its derivative products. The implementation of this downstream strategy is expected to positively impact the welfare of oyster mushroom farmers and the sustainability of the local food industry.